Історія виникнення ботанічного саду Дніпропетровського національного університету ім. Олеся Гончара - Kavun, M.E.; Savchuk, V.S.; Opanasenko, V.F.; Pachomov, A.E. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
On the base of little-known archives and also published sources the process of foundation of the botanical gardens of Oles’ Gonchar Dnipropetrovs’k National University was researched. The initiatives of Ekaterinoslav intellectuals which concerned the process of foundation of the botanical gardens were studied.